Determinants of Local Food Consumption Among Shoppers in Traditional Markets - Arsil, Poppy; h, Ardiansya; Yanto, Tri (International Journal of Engineering and Technology, 2018)
This study applies the conceptual framework of sustainable food consumption to investigate the determinant factors of local food consumption in Indonesia. The roles of personal characteristics, such as personal values, information, and knowledge, as well as of behavioral control, were also included in the model. Factor analysis and multiple regression were used to identify the predictors of local food consumption and to develop constructs to identify the determinant factors that affected local food consumption behaviour. The empirical research was based on a survey using a structured questionnaire given to 300 respondents who shop at traditional markets in urban and rural areas. Using factor analysis, 60.351% of the variance to purchase local food at traditional markets was explained by 12 emerging factors. Behavioral control, affective attitude, and personal norms influence behavioral intention among shoppers in traditional markets while behavioral control and personal norms are significant dimensions for attitude. The findings suggest that the factors can be used to increase local food consumption among shoppers in traditional markets.